Performansi Pipa Bersirip Alat Penukar Kalor Udara-Tanah Menggunakan Siklus Terbuka - Manik, Terang UHSG; Sitorus, Tulus Burhanuddin; Situmorang, Mangontang (TALENTA Publisher, 2021)
In heat exchanger analysis using the Earth Air Heat Exchanger method, the overall heat transfer coefficient is known. This tool uses tubes in its design. The weakness of tube and plate type heat exchangers is the relatively low heat transfer coefficient, which can only reach a maximum of 60%. Therefore, a method to improve the heat transfer efficiency is using a fin. The purpose of this study is to calculate and compare the effectiveness (Îµ) value of experimental and theoretical of the Earth Air Heat Exchanger, as well as to find out the value of the coefficient of performance. The result showed that the average COP value of the experimental result is 0.63 at a speed of 1 m / s, 0.54 at the speed of 2 m / s, and 0.75 at the speed of 3 m / s, while theoretically is 0 , 73 at 1 m / s, 0.57 at 2 m / s, and 0.80 at 3m / s. For the value of the average effectiveness of the experimental results obtained 0.85 at the speed of 1 m / s, 0.93 at the speed of 2 m / s, and 0.89 at the speed of 3 m / s, while the theoretical result is 0.995 at the speed of 1 m / s, 0.997 at 2 m / s, and 0.998 at 3 m / s.